نوع جديد ومهاجر من السرطانات البحرية في المياه الشاطئية السورية- Matuta victor (Fabricius, 1781) (Crustacea: Decapoda: Brachyura: Matutidae). - زيني أديب; الحسن حسان (Latakia University Journal -Biological Sciences Series, 2018)
Eleven specimens of the moon crab Matuta victor (Fabricius, 1781) were recorded from the eastern coast of the Mediterranean Sea in Syria . The most adult specimens are males, one female only. They were recently collected by Fishermen from the coast of Tartus , Banias and Lattakia at about 8 to 12m deep. This lessepsian migrant is the first species from the family Matutidae reported in the Syrian water so far. تم جمع أحد عشر فرداً من القشري سرطان القمر Matuta victor (Fabricius, 1781) وسجل وجوده في الجزء الشرقي من البحر المتوسط من سورية. معظم العينات من الذكور ولم يسجل سوى أنثى واحدة. جمعت العينات من قبل صيادي الأسماك من شاطئ طرطوس وبانياس واللاذقية على أعماق من 8-12 متر. هذا النوع المهاجر عبر قناة السويس (ليسبسياني) من فصيلة Mututidae يسجل لأول مرة في المياه الشاطئية السورية.